2016
DOI: 10.1097/md.0000000000002666
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From a Case of Gastric Cancer After Liver Transplantation for Hepatocellular Carcinoma

Abstract: Nowadays, de novo malignancies have become an important cause of death after transplantation. According to the accumulation of cases with liver transplantation, the incidence of de novo gastric cancer is anticipated to increase among liver transplant recipients in the near future, especially in some East Asian countries where both liver diseases requiring liver transplantation and gastric cancer are major burdens. Unfortunately, there is limited information regarding the relationship between de novo gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 43 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…The development and progression of tumors are characterized by evasion of immune responses, including tumor escape mediated through immune checkpoint pathways [37][38][39][40]. The etiology of GC/ GEJC in some patients has been associated with immunosuppressive treatment for organ transplants and viral infections [41,42], suggesting that the immune system plays an important role in tumor control. Furthermore, key immune checkpoint proteins, including cytotoxic Tlymphocyte antigen 4 (CTLA-4), indoleamine 2,3-dioxygenase (IDO), Tcell immunoglobulin and mucin domain-containing protein 3, lymphocyte activation gene 3 protein (LAG-3), and PD-1, are overexpressed on immune cells in patients with GC/GEJC, suggesting a role for tumorinduced T-cell exhaustion in disease progression [43][44][45].…”
Section: Rationale For Checkpoint Inhibitors In Gc/gejcmentioning
confidence: 99%
“…The development and progression of tumors are characterized by evasion of immune responses, including tumor escape mediated through immune checkpoint pathways [37][38][39][40]. The etiology of GC/ GEJC in some patients has been associated with immunosuppressive treatment for organ transplants and viral infections [41,42], suggesting that the immune system plays an important role in tumor control. Furthermore, key immune checkpoint proteins, including cytotoxic Tlymphocyte antigen 4 (CTLA-4), indoleamine 2,3-dioxygenase (IDO), Tcell immunoglobulin and mucin domain-containing protein 3, lymphocyte activation gene 3 protein (LAG-3), and PD-1, are overexpressed on immune cells in patients with GC/GEJC, suggesting a role for tumorinduced T-cell exhaustion in disease progression [43][44][45].…”
Section: Rationale For Checkpoint Inhibitors In Gc/gejcmentioning
confidence: 99%
“…The impaired anti-carcinogenesis actions of T lymphocytes, macrophages, and natural killer cells for immune surveillance, delaying tumor progression, and preventing angiogenesis, vascular invasion, and metastasis have been proposed as the mechanisms by which tumorgenesis develops in patients with immunosuppressive therapy [ 9 ]. Helicobacter pylori and EBV infections have also been known as risk factors for gastric cancer in patients with LTx, with the eradication of these microorganisms possibly being necessary for reducing the risk of de novo gastric cancer in transplant recipients [ 10 ]. However, the present patient exhibited no obvious specific findings to suspect Helicobacter pylori infection, with his tumor specimen being immunopathologically negative for EBV.…”
Section: Discussionmentioning
confidence: 99%
“…As described earlier, prolonged immunosuppressive therapy may increase the risk of developing de novo malignancy, with one study identifying tacrolimus as an independent risk factor for post-transplant malignancy developing in patients who had undergone renal transplantation [ 14 ]. Indeed, studies have showed that tacrolimus was associated with the risk of solid organ tumors, not limited to gastric cancer [ 10 ]. Given that the present case had been receiving tacrolimus for approximately 19 years after LTx, such long-term use of tacrolimus might have contributed to the development of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Curative treatment should be considered even for gastric cancer after transplantation if the performance status and cardiopulmonary function of each patient are considered medically fit [ 6 , 7 ]. The guideline of the Japanese Research Society for Gastric Cancer recommends distal gastrectomy with dissection of lymph nodes around the stomach and left gastric artery as a radical operation for gastric cancer with submucosal invasion [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…De novo gastric cancer is one of these malignancies and there are several reports concerning with its treatment such gastrectomy [ [2] , [3] , [4] , [5] , [6] ]. Although surgery are the mainstay treatments for de novo gastric cancer just as with malignancy that develops in the general population [ 6 , 7 ], there are some issues to be considered when gastrectomy would be attempted especially after liver transplantation: Severe postoperative adhesion and anatomical rearrangement due to vessel reconstruction could lead to vascular injuries. Moreover, if splenectomy was performed with liver transplantation, a dissection between the stomach and splenic hilum might impair a blood supply to the stomach and insufficient blood supply to remnant stomach after gastrectomy is one of risks of anastomotic leakages and gastric necrosis.…”
Section: Introductionmentioning
confidence: 99%